Specialist inpatient services for people with learning disabilities across the four countries of the UK. Issue 4 (3rd October 2016) - Hatton, Chris
Abstract : Purpose: The purpose of this paper is to compare data from national censuses on specialist inpatient service use by people with learning disabilities across England, Scotland, Wales and Northern Ireland. Design/methodology/approach: National statistics (England, Scotland, Wales, Northern Ireland) reporting inpatient service censuses including people with learning disabilities were accessed, with data extracted on trends over time, rate of service use, young people and length of stay. Findings: The number and rate of people with learning disabilities in specialist inpatient services varied across the UK: 230 people in Scotland (rate 4.88 per 100, 000 population); 3, 250 people in England (5.48); 183 people in Wales (5.90); 144 people in Northern Ireland (7.82). The number of people in inpatient services in Northern Ireland halved over four years, in other areas reductions were modest. Between 5 and 8 per cent of people in inpatient services were children/young people. Median length of stay in the person's current inpatient service varied: 19 months in England; 33 months in Scotland; three to five years in Northern Ireland. Social implications: Different parts of the UK vary in the scale of their specialist inpatient services for people with learning disabilities. With the exception of Northern Ireland, which may still be in the last stages of completing a "regular" deinstitutionalisation programme, strong policy prescriptions for substantial reductions in specialist inpatient services are currently only resulting in modest reductions. Originality/value: This paper is a first attempt to compare national inpatient service statistics across the UK. With increasing divergence of health and social service systems, further comparative analyses of services for people with learning disabilities are needed.